In-Hospital Outcomes of Chronic Total Occlusion Percutaneous Coronary Interventions in Patients With Prior Coronary Artery Bypass Graft Surgery: Insights From an International Multicenter Chronic Total Occlusion Registry. (March 2019) - Tajti, Peter; Karmpaliotis, Dimitri; Alaswad, Khaldoon; Jaffer, Farouc A.; Yeh, Robert W.; Patel, Mitul; Mahmud, Ehtisham; Choi, James W.; Burke, M. Nicholas; Doing, Anthony H.; Dattilo, Phil; Toma, Catalin; et al.
Abstract : Background: We examined the procedural outcomes of chronic total occlusions (CTO) percutaneous coronary interventions in patients with prior coronary artery bypass graft surgery (CABG). Methods and Results: We compared the clinical, angiographic characteristics and outcomes of 3486 CTO interventions performed in patients with (n=1101) and without (n=2317) prior CABG at 21 centers. Prior CABG patients (32% of total cohort) were older (67±9 versus 63±10 years; P <0.001) and had more comorbidities and lower left ventricular ejection fraction (50% [40–58] versus 55% [45–60]; P <0.001). The CTO target vessel in prior CABG patients was the right coronary artery (56%), circumflex (26%), and left anterior descending artery (17%). The mean J-CTO (2.9±1.2 versus 2.2±1.3; P <0.001) and PROGRESS-CTO (Prospective Global Registry for the Study of Chronic Total Occlusion Intervention; 1.5±1.1 versus 1.2±1.0; P <0.001) score was higher in prior CABG patients. Retrograde (53% versus 30%, P <0.001) and antegrade dissection reentry (35% versus 28%; P <0.001) techniques were used more frequently in prior CABG patients. Prior CABG patients had lower technical (84% versus 89%; P <0.001) and procedural (82% versus 87%, P <0.001) success, but similar incidence of in-hospital major complications (3.1% versus 2.5%; P =0.287). In-hospital mortality (1% versus 0.4%; P =0.016) and coronary perforation (7.1% versus 3.1%; P <0.001) occurred more frequently in prior CABG patients, however, CABG patients had a lower incidence of pericardial tamponade (0.1% versus 1.0%; P =0.002) and pericardiocentesis (0% versus 1.3%; P <0.001). Conclusions: In a large multicenter CTO percutaneous coronary interventions registry, prior CABG patients had lower success rate but similar overall risk for complications, although mortality was higher and the incidence of tamponade was lower. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02061436. Abstract : Supplemental Digital Content is available in the text.